Strategia rozwoju lokalnego jako narzędzie rozwoju agrobiznesu i jego konkurencyjności - Wiatrak, Andrzej Piotr (Strategy of Local Development as An Instrument of Agribusiness Development and Its Competitiveness, 2006)
In the conditions of the rural communes in Poland the basis of economy is agribusiness which development - with regard to low earnings - is possible owing to support on local scale and the preparation of strategy based on possessing productive resources and acceptance of the inhabitants. In this article the author introduces: strategy essence of local development, position the agribusiness of in strategy of local development and its conditioning and also success conditions of agribusiness firms on local scale.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 2, s. 470-475